Monitoring sand particle concentration in multiphase flow using acoustic emission technology - El-Alej, Mohamed Essid (Cranfield University, 2014)
Multiphase flow is the simultaneous flow of two or several phases through a system such as a pipe. This common phenomenon can be found in the petroleum and chemical engineering industrial fields. Transport of sand particles in multiphase production has attracted considerable attention given sand production is a common problem especially to the oil and gas industry. The sand production causes loss of pipe wall thickness which can lead to expensive failures and loss of production time. Build-up of sand in the system can result in blockage and further hamper production. Monitoring of multiphase flow is a process that has been established over several decades. This thesis reports an assessment of the application of Acoustic Emission (AE) technology as an alternative online technique to monitoring of sand particles under multiphase flow conditions in a horizontal pipe. The research was conducted on a purpose built test rig with the purpose of establishing a relation between AE activity and sand concentration under different multiphase flow conditions. The investigation consisted of five experimental tests. The initial experiment was performed to provide a basis for the application of AE technology to detect sand particle impact prior to performing tests in multiphase flow conditions. Further investigations are reported on two phase air-sand, water-sand and air- water-sand three-phase flows in a horizontal pipe for different superficial gas velocities (VSG), superficial liquid velocities (VSL) and sand concentrations (SC). The experimental findings clearly showed a correlation exists between AE energy levels and multiphase flow parameters, such as superficial liquid velocity (VSL), superficial gas velocity (VSG), sand concentration and sand minimum transport condition (MTC).
Keywords: Multiphase flow; acoustic emission; pipeline monitoring; sand monitoring; sand minimum transport condition (MTC)